Manejo alimentar para Curimatã-pacu Prochilodus argenteus (SPIX e AGASSIZ, 1829) envolvendo ciclos curtos de restrição alimentar e realimentação - Reis Neto, Jurandyr (2019)
The objective of this study was to evaluate the effects of restriction and feedback regimes on productive performance and physiological aspects in curimatã-pacu fingerlings. A total of 140 fish were used, with 2.85 ± 0.04g, and 20 boxes (130L) were distributed in a completely randomized water recirculation system with four treatments and five replicates for 64 days. The treatments were: T1 - uninterrupted feed (7F:0R), T2 - feeding six days and one day of fasting (6F:1R), T3 - feeding five days and two days of restriction (5F:2R) and T4 - feeding four days and three days of deprivation (4F:3R). Feeding was provided three times a day (08:00, 12:00 and 16:00) to apparent satiety with 45% CP feed, obeying the feeding days of each treatment. The physical-chemical parameters of the water were measured daily. The performance variables evaluated were: final weight (FW), weight gain (WG), total length (TL), standard length (SL), body width (BW), body height (BH), length of head (LH), specific growth rate (SGR), average feed intake (AFI), apparent feed conversion (AFC), rate of protein efficiency (PER), profile index (PI), head index (HI), survival (Surv) and heterogeneous growth (HG). The physiological data analyzed were: hepatosomatic and viscerosomatic indexes (HSI and VSI), body composition, bowel histology, blood glucose and defense cells, antioxidant capacity (SOD, CAT and GST), malondialdehyde (MDA) and cholinesterase activity (AChE and BuChE). The results were submitted to analysis of variance and, with significant differences among averages, a Tukey test was used at 5%. 6F:1R and 5F:2R showed values of FW, WG, TL, SL and LH similar the 7F:0R, differing (p<0.05) from 4F:3R that showed worse results indicating low organism adaptability to longer periods in this stage of life. The absence of hyperphagia resulted in lower AFI (p=0.0000) in the fasted groups. The 5F:2R AFC was similar the 7F:0R, which differed (p=0.0116) from the others. HG has been softened to 4A: 3R. The 5F:2R and 4F:3R groups had lower lipid levels and dry matter (p<0.01) and higher protein concentrations (p<0.01), showing low aggressiveness and good adaptation to these regimes. Fasting caused histomorphological changes in the anterior intestine as a way of adaptation. Glucose, lymphocytes and monocytes did not differ between different dietary regimes. Hepatic SOD was higher (p=0.0332) in the groups under restriction. BuChE revealed higher activity (p<0.05) in the brain and muscle of the 7F:0R. The adoption of up to two days of fasting per week can be applied to the feeding of this species at this stage of life without significant interference with performance and severe physiological consequences.